The administrative-legal methods of compensation of damage (Journal of actual problems of jurisprudence, 2018)
This article deals with the problems of administrative and legal methods of compensation of damage. In the article the authors identify particular attention to administrative and authoritative restore as a legal institution of administrative law enforcement.Key words: administrative responsibility, administrative enforcement, administrative recovery harm.